Design considerations of navigation satellite constellation for low Earth orbit - Praks, Jaan; Saleem, Zainab; Mayank; Çelikbilek, Kaan; Prol, Fabricio; Sharma, Shikha; Kuusniemi, Heidi; Ferranti, Luca; Lohan, Elena Simona; Pinell, Christina; Kaasalainen, Sanna; Bhuiyan, M. Zahidul H. (IEEE, 2023)
In this study we provide an overview of feasibility assessment of Low Earth Orbit Position, Timing and Navigation (LEO-PNT) satellite system. We discuss several aspects of such a design, such as signal design, accuracy assessment, satellite constellation design, satellite payload design and satellite platform design. We conclude, that such a system is feasible and provide general parameters for implementation.
Keywords: fi=Tietotekniikka|en=Computer Science|